PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI DALAM PEMBELAJARAN IPAS PADA MATERI MENJADI PAHLAWAN LINGKUNGAN KELAS IV SEKOLAH DASAR - Nur Anisah Nasution; Aprilia, Rapita; Kumala Sari, Cut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by issues in Natural and Social Sciences (IPAS) learning in Class IV at SDN 10 Langsa. Educators still predominantly rely on textbooks as the main learning source, causing students to tend to lose focus during the learning process. Therefore, this study aims to develop a learning medium tailored to students' needs, test the feasibility, and ensure the practicality of an animated video learning medium based on Canva and CapCut applications covering the topic "Becoming Environmental Heroes" (Menjadi Pahlawan Lingkungan). This Research and Development (R&D) study employed the 4D model (Define, Design, Develop, Disseminate). Data were collected through observations of IPAS learning in Class IV, interviews with educators, expert validation assessments, as well as response questionnaires from both the educator and students. The validation results indicated that the product was declared "Very Feasible" based on assessments by material experts (96.87%), language experts (100%), and media experts (82.5%). Furthermore, the product achieved a "Very Practical" level of practicality, obtaining a 97.5% score from an educator practitioner's response questionnaire and a 91.71% score from 19 students' responses. Consequently, this animated video learning medium is proven to be highly feasible and practical for use in IPAS learning in elementary schools. Keywords: Animated Video, Canva and CapCut, IPAS Learning, Becoming Environmental Heroes, Research and Development (R&D)